Magistrate’s Courts in the Criminal Justice System - PESTSOV, Ruslan G.; RYABOVOLENKO, Irina V.; KITSAN, Yuriy I.; MELNYK, Roman V.; KRAVCHUK, Oleg V. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).26, 2019)
The article is dedicated to the historical development of the institution of the magistrate’s courts in Ukraine and in the world. The paper describes the appearance of the first magistrate’s courts in the judicial system. The analysis of legislation of European countries regarding the legal status of magistrates is performed and the authority of magistrate’s courts in punitive proceedings is explored. The development of magistrate’s courts on the territory of modern Ukraine in the 19th century was reviewed. The question was raised about the introduction of magistrates in the current Ukrainian judicial system.